Implementasi Ecogreen Packaging dalam Pengembangan Packaging Unggulan Kampung Industri Tempe Sanan - Surya, Eka Putri; Ningrum, Linda Agustin; Aruna, Alby; Prasetyo, Abdul Rahman; Marcelliantika, Adinda; Wijaya, Ginanjar Atma (IAI Nasional Laa Roiba Bogor, 2024)
The implementation of Ecogreen Packaging in the development of premium packaging at the Sanan Tempe Industrial Village aims to enhance the value of tempe products through the use of environmentally friendly packaging. This program combines modern packaging technology with sustainability principles to produce packaging that is both attractive and sustainable. Methods include research and development of packaging design, technical training for tempe producers, and evaluation of packaging effectiveness through consumer feedback. The results show increased consumer satisfaction and reduced environmental impact from traditional packaging use. The implementation of Ecogreen Packaging is expected to support the sustainability of the tempe industry and enhance the competitiveness of products in the global market.